The Mediating Role of Motivation on the Relationship of Job Characteristics and Job Training on Employee Performance - Luthfiani, Indanaa; Rijanti, Tristiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aimed to investigate the contribution of job characteristics and job training to employee performance through the mediating role of work motivation. Data were collected through questionnaires with saturated sampling techniques. Data were analyzed using multiple regression analysis and the Sobel test, through the IBM SPSS software version 23. The results showed that job characteristics and job training partially had a positive and significant effect on motivation. Furthermore, job characteristics, job training, and motivation partially had a positive and significant impact on employee performance. This study concludes that motivation has been proven to play a role as a mediating in the influence of both job characteristics and job training on employee performance.